Development of Audio Visual Learning Media Based on Canva Application for Class VII Subject of Society at SMP Negeri 6 Sigi - Bumbungan, Ferdi; Juraid, Juraid; Misnah, Misnah (Journal of Education Method and Learning Strategy, 2024)
The important role of education is to improve the quality of human resources through effective, efficient and enjoyable learning, so that students are able to absorb information optimally. The media used in learning has not maximized technological developments so that a contextual, creative and collaborative learning experience has not been achieved. This research aims to produce Canva-based audio visual learning media. This type of research uses Research and Development (R&) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subject of this research is the development of audio visual learning media based on the Canva application for class VII A students, totaling 30 students in one class. The data collection technique used in this research was carried out using an expert questionnaire consisting of material experts, media experts, and a questionnaire sheet on student responses to the learning media being developed. The research results showed that the feasibility of Canva-based audio visual learning media was assessed by one media expert and a material expert. Based on the assessment, the results obtained from material experts were 95% and included in the very feasible category, while those from media experts were 74.30% and included in the feasible category. Overall, media can be used for the learning process.